SYNTHESIS; CHARACTERIZATION AND CYTOTOXIC ACTIVITY EVALUATION OF CYCLOPALLADATED COMPOUNDS CONTAINING ORTHOMETALLATED BENZALDEHYDEOXIME AND ETHYLENETHIOUREA AS LIGANDS - Thomazella, Nathalia A. [UNESP] (2018)
The halide bridge cleavage reaction of the [Pd(C-2,N-bzox)(mu-Cl)](2). compound (bzox = benzaldehydeoxime) with ethylenethiourea (L) in the 1:2 molar ratio at room temperature yielded the cyclopalladated compound [Pd(C-2,N-bzox)(Cl)(L)] (1) whose replacement of the halide group by the addition of suitable salts afforded compounds of general formulae [Pd((C-2,N-bzox)(X)(L)] = {X = Br- (2), I-(3)}. All compounds were characterized by melting point, elemental analyses, infrared and H-1- and C-13H-1-NMR spectroscopies revealing the complexes formation with the oxime coordinated to Pd(II) as C,N-chelating and the ethylenethiourea as a monodentate ligand via the sulfur atom. Hie cytotoxicity of cyclopalladated compounds has been evaluated in vitro against murine mammary tumor cell (LM3) showing cytotoxic activity similar to cisplatin.